(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The goal of any service provider is to satisfy the customer expectations in order to create a brand loyalty. However, no service provider can escape from the service errors as humans are involved in service delivery. Since the production and consumption of services usually occurs concurrently, the quality of a service is dependent upon the deliverability of the service provider and the recipient’s utility. Thus, in order to overcome the limitation of inevitable errors, service providers must be concerned with service recovery. As attracting new customers is costly as compared to retaining existing customers, it becomes another important reason for service providers to must try hard for efficient service recovery. This empirical investigation is designed to test effective recovery processes for service failures in e-hailing by studying the relationship between compensation, apology, and response time on perceived justice, service recovery satisfaction, and repurchase intention of the customer. Our sample consist 160 students from University of Delhi, India, who are active e-hailing service users. The findings indicate that all three e-hailing service recovery attributes appear to be key in creating satisfied customers based on their effects on perceived justice.